2018
DOI: 10.1080/03075079.2018.1437722
|View full text |Cite
|
Sign up to set email alerts
|

Why so slow? The school-to-work transition in Italy

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 30 publications
3
63
0
Order By: Relevance
“…Furthermore, many students do not attend the courses and the programmes for many exams are too wide, especially for the so-called rock exams, which are almost impossible to pass due to, among other reasons, the teaching load in excess of that provided by the relevant training credits (Pastore, 2019). In this paper, we focus only on the time from the end of studies to the attainment of a stable job, since, unfortunately, information on education is not sufficiently detailed in the EU-SILC data bank.…”
Section: Methodsology and Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, many students do not attend the courses and the programmes for many exams are too wide, especially for the so-called rock exams, which are almost impossible to pass due to, among other reasons, the teaching load in excess of that provided by the relevant training credits (Pastore, 2019). In this paper, we focus only on the time from the end of studies to the attainment of a stable job, since, unfortunately, information on education is not sufficiently detailed in the EU-SILC data bank.…”
Section: Methodsology and Datamentioning
confidence: 99%
“…Our analysis integrates and develops the analysis of the Italian STWT regime, which has already been characterized as essentially extremely slow (Pastore, 2019). We contribute to the analysis of the Italian model by providing new and detailed evidence and by looking at the specific determinants at an individual and macroeconomic level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These SWT regimes overlap with the identification of welfare FRANCESCO PASTORE | Why is youth unemployment so high and different across countries? state regimes-social democratic, conservative, liberal-with the addition of the so-called Latin Rim (southern European countries) [4], and former socialist countries.…”
Section: Discussion Of Pros and Consmentioning
confidence: 99%
“…Survey evidence from the United Kingdom shows that two-thirds of teachers and secondary school students in England agreed that short work experience placements helped in career decision-making and navigation (Mann and Dawkins, 2014 [32]). The EU Partnership-Project on Work-based Learning and Teaching (2015 [33]) surveyed teachers in nine European Union countries and found that in some countries, students said they appreciated WBL not only as a means of gaining skills but also as a mechanism to ensure that they were making well informed decisions. However, students often expressed the wish that learning at schools and in the workplace were better aligned.…”
mentioning
confidence: 99%